Respiratory viruses in patients with influenza-like illness in Senegal: Focus on human respiratory adenoviruses - Niang, Mbayame Ndiaye (PLoS One, 2017)
BACKGROUND: Human adenoviruses (HAdVs) are highly contagious pathogens that are associated with a wide spectrum of human illnesses involving the respiratory tract. In the present study, we investigate the epidemiologic and viral molecular features of HAdVs circulating in Senegal after 4 consecutive years of sentinel surveillance of influenza-like Illness cases. METHODOLOGY AND RESULTS: From January 2012 to December 2015 swabs were collected from consenting ILI outpatients. Adenoviral detection is performed by rRT-PCR with the Anyplex(™) II RV16 Detection kit (Seegene) and molecular characterization was performed using a partial hexon gene sequence. 6381 samples were collected. More than half of patients (51.7%; 3297/6381) were children of ≤ 5 years. 1967 (30.8%) were positive for HAdV with 1561 (79.4%) found in co-infection with at least one another respiratory virus. The most common co-detections were with influenza viruses (53.1%; 1045/1967), rhinoviruses (30%; 591/1967), enteroviruses (18.5%; 364/1967) and RSV (13.5%; 266/1967). Children under 5 were the most infected group (62.2%; 1224/1967; p <0.05). We noted that HAdV was detected throughout the year at a high level with detection peaks of different amplitudes without any clear seasonality. Phylogenetic analysis revealed species HAdV-C in majority, species HAdV-B and one HAdV- 4 genome type. The 9 HAdV-B species like strains from Senegal grouped with genome types HAdV-7, HAdV-55 and HAdV-11 as shown by a phylogenetic branch with a high bootstrap value of (88%). CONCLUSION: In conclusion, the results of the present study suggest strong year-round HAdV activity in Senegal, especially in children up to 5 years of age. Molecular studies revealed that the dominant species in circulation in patients with ILI appears to be HAdV-C and HAdV-B species. The circulation of though HAdV-7 and HAdV-55 genome types is of note as these serotypes are recognized causes of more severe and even fatal acute respiratory infections.